GODS AND HUMANS: LIVING UNDER THE SAME ROOF - A. V. Baulo; А. В. Бауло (IAET SB RAS, 2016)
The article integrates the growing knowledge of domestic (family) shrines of the northern Mansi living in the Berezovo District, Khanty-Mansi-Yugra District. Variants of location and composition of ritual paraphernalia are listed. Religious traditions and recent changes they have undergone are discussed. New types of sacrificial cloths, the arrangement of the figures of deities, the characters of the shamanistic practices, unusual ancient artifacts cast of bronze, and late 18th-century silver items are described. Статья посвящена современному состоянию домашних (семейных) святилищ северных манси, проживающих на территории Березовского р-на ХМАО–Югры. Описаны варианты расположения и состав культовых атрибутов. Отмечены сохраняющиеся в религиозно-обрядовой сфере традиции и произошедшие в последние годы изменения. Вводятся в научный оборот ранее неизвестные варианты жертвенных покрывал, способы формирования фигур божеств, персонажи шаманской практики, уникальные образцы древнего бронзолитейного производства и тобольского среброделия конца XVIII в.